Study of metabolic changes-glycoprotein and phospholipids levels in patients of malaria - Tyagi, Rupal A.; Tyagi, Amit G.; Choudhary, Prema Ram; Shekhawat, Jaidev Singh (International Journal of Research in Medical Sciences, 2017)
Background: In erythrocytic stage, malarial parasites meet their high glucose requirement only by modulating the host cell membrane by increasing transport of sugar across the host cell membrane. This leads to a transmembrane gradient of the substrate and finally leading to alterations of metabolic changes and permeability of RBC membrane. Therefore, the aim of present study was to determine the parameters which reflect the status of RBC membrane and their association with the severity of malaria in a large cohort of known patients of malaria, which was caused by the Plasmodium Species. Methods: Blood sample were collected in EDTA bulb at the time of admission (day-1) and on third day (day-3). The samples were analyzed within 24 hours of collection. Erythrocytic total phospholipid is measured by modified connerty method, Total sialic acid (TSA) is measured by TBA/dimethyl sulphoxide method. Results: The mean levels of erythrocytic phospholipid, plasma TSA and PBSA in the cases of malaria were significantly increase (P<0.001) as compared to those in the control group. In the follow up study the same parameters were studied in patients post anti-malarial treatment day-3. The level of erythrocyte phospholipid, plasma TSA and PBSA were reversed. Conclusions: On the basis of the present study it is suggested that the anti-malarial drug regimen must be supported by antioxidants and trace elements supplementation to improve the status of deviated biochemical parameters towards normalcy.